BALANCED SCORECARD ANALYSIS AS A PERFORMANCE MEASUREMENT AT UB HOTEL - PUJAKANEO, RUSMIAN NUZULUL (Jurnal Ilmiah Mahasiswa FEB, 2016)
The increasing tourism growth rate accompanied with development of hospitality industry led to the increase of competition between entrepreneurs. This encourages entrepreneur to prepare the best strategies in order to compete and be the best among its competitors. To achieve its goals, manager needs to prepare the right strategy. The Balanced Scorecard helps the manager to translate the organization’s mission and strategy into a comprehensive set of performance measures. Therefore, as a business unit that operates in the field of services, UB Hotel must be able to provide the best service to guests. Providing the best service for customers, UB Hotel needs to do a performance evaluation to determine the extent to which performance poses impact on guests visit. Using qualitative approach, this research is expected to produce an in-depth description of the phenomena using interview, writing, and the observable behavior of an individual, group, and organizations in the context and may reveal a complete, comprehensive and holistic/ comprehensive understanding. After analyzing the performance at UB Hotel using the Balanced Scorecard, the researcher found that the financial performance of UB Hotel is considered satisfying, the customer perspective on UB Hotel is bad, the operational service efficiency, and, in post-sales  service benchmark,  customer  relationship  is  also  bad,  and  the  learning  and growth perspective at UB Hotel is good. From the analysis results, the company needs improve these aspects such as considering marketing strategy, increasing employee and customer retention, customer acquition, customer satisfaction and staying experience at the hotel, improving both ROA and Operational profit margin, and  reviewing the room rates offered to the customer.Keywords:  Balanced  Scorecard,  Financial,  Customer,  Internal  Business  Process,  and Learning & Growth